Conceptualisation of borders in German-Czech organisations - Marx, Christoph; Nekula, Marek (Bohemica Olomucensia, 2013)
Language plays in conceptualisation of the border very imporant role. The reasons can be summarized in this way: (1) emphasizing of language border enables the localization without obligate evocation of the political, systemic border; the border is represented by Czech-German language border which enables ideologically proposed overcrossing of the political and systemic border. (2) The border overcrossing is in the analysed organisations approached by declaring the relations of both languages and by thoroughgoing bilinguism in the external communication, i.e. the border is being maked visible through the simultaneous existence of both languages and it is being overcame in the translation. (3) It is not possible to understand the analysed language areas as bilingual areas on the base of their depiction, because there are contact interactions between users of Czech and German language in the area. This is the case of employees of that border crossing organisations wherein the communication in non-mother tongue became the everyday necessity.